Overview of retail investment instruments of the Russian economy - M. E. Kosov (Вестник университета, 2024)
Features of the current stage of development of Russia increase the relevance of studying problems associated with the expansion of internal sources of financing economic growth, one of which may be citizens’ savings. To attract private capital more widely, the national financial system can and should provide a large range of tools for private investors that meet the needs of citizens in terms of profitability and safety of funds. The paper has considered the key tools of retail investment, which are currently widely used in domestic practice. Alternative ways of private investment have also been explored. They can be applied depending on the needs of specific actors, market participants, or citizens. The development of a line of instruments for the retail investment – deposits, long-term individual investment accounts, products of research and production associations, insurance products, etc., their availability is one of the conditions for the effective functioning of the domestic financial market and, as a consequence, the Russian economy as a whole. The analysis of the essence, trends, opportunities, and risks of the retail investment instruments will allow us to assess the effectiveness of the activities of financial regulators in this area and identify promising and appropriate areas for its improvement.